Inhibition of HL-60 cell growth via cell cycle arrest and apoptosis induction by a cycloartane–labdane heterodimer from Pseudolarix amabilis. Issue 9 (1st February 2016) - Tian, Xinhui; Yang, Niao; Li, Bo; Zhang, Jianping; Xu, Xike; Yue, Rongcai; Li, Huiliang; Chen, Liping; Shen, Yunheng; Zhang, Weidong
Abstract : A cycloartane–labdane heterodimer pseudolaridimer C (1 ) was isolated from Pseudolarix amabilis . It exerted a cytotoxicity effect on HL-60 cells by arresting the cell cycle in the G2/M phase and inducing caspase-dependent apoptosis. Abstract : Pseudolaridimer C (1 ), a rarely encountered cycloartane–labdane Diels–Alder adduct was isolated from the cones of Pseudolarix amabilis . The structure and absolute configuration of1 were established by comprehensive NMR and CD spectral analysis. The WST-8 assay indicated that1 time and dose dependently inhibited the proliferation of human leukemia cells HL-60 at 1–10 μM. DAPI and Annexin V-FITC/PI double staining method, and DNA ladder experiments all proved that1 had significant dose-dependent effects on HL-60 cell apoptosis. A further mechanism study indicated that the apoptosis was associated with the cell cycle arrest during the G2/M phase, and the activation of caspase-9, -3, -7, and poly-(ADP-ribose)-polymerase (PARP).